(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Osteoarthritis is a chronic degenerative joint disease that is common among older people. The article discusses the pathogenetic mechanisms of osteoarthritis, its impact on the functional capabilities of patients, and modern rehabilitation strategies. Particular attention is paid to exercise therapy, physiotherapy, drug therapy, and psychoemotional support as key components of comprehensive disease management. A systematic approach to improving the quality of life of patients and reducing the degree of disability is presented.